TATA KELOLA TINGKAT LAYANAN SISTEM INFORMASI PEMESANAN TIKET MENGGUNAKAN KERANGKA KERJA COBIT 4.1 PADA ARNES SHUTTLE CABANG KOTA BANDUNG - Syafariani, R.Fenny; Nandapratama, Gilang (PETIR, 2019)
All the development of information systems and computer technology very fast. It can be seen in everyday life where people in this world are utilizing the computer as a tool to complete their job. Information systems are used to provide facilities for a company in general. And the special to facilitate the service for booking tickets at Arnes Shuttle Branch Bandung. Information technology required by Arnes Shuttle is related to information technology ticket booking system . The information system will allow a company to run its business processes . But after research by observation and interviews are still found weaknesses in the current system . The problems that exist in the ticket booking information system is the frequent occurrence of error or can’t be processed that cause slow service For the management of information systems need to service level governance information system using the COBIT framework 4.1 (Control Objective for Information and Related Technology).